Risk factors and trends in neonatal mortality in NICU in a tertiary care hospital in India - Ukkali, Sadashiva B; Kulkarni, Nagamani; Badsheshi, Punitha; Naganoor, Ravindra; Thobbi, Achyut (Indian Journal of Child Health, 2024)
Introduction: The most vulnerable period of human life is neonatal period, which accounts for most of the morbidities and mortalities. Most of them are preventable with adequate health-care facilities.Objectives: The aim of the study was to determine the trends of neonatal mortality and identify the risk factors, most of which are preventable and measure the progress of health-care services.Methods: A retrospective study was conducted in neonatal intensive care unit (NICU) of Al-Ameen Children Hospital (AMCH) Vijayapura, Karnataka, India. Data were extracted from paper medical records at AMCH of a period of 1 year and digitized. Data obtained included age, sex and birth weight, place of delivery, morbidity profile, mortality profile, diagnosis, and period of stay in NICU.Results: A total of 648 neonates were admitted in NICU during the study period of 1-year duration, between January and December 2021. A total of 382 (58.9%) infants were discharged on recovery, 65 (10.3%) were referred due to unavailability of advanced surgical intervention, 39 (6%) were discharged against medical advice, 162 (25%) died due to various reasons. Male neonatal deaths outnumbered female neonates (56.8%). Among the total neonatal deaths, 82 (50.6%) were preterm neonates, 73 (45.1%) were term neonates and 7 (4.3%) were post-term neonates. It was noticed that among neonatal deaths, 87 (54.3%) babies were out-born and 75 (46.2%) babies were inborn. In this study, it was noticed that the mortality percentage of the neonate falling in the category of 1.5–1.9 kg was high compared to other categories. In our study, respiratory distress syndrome was the main cause of mortality accounting for 19.1% (31 cases) of total cases and prematurity was the most common risk factor.Conclusion: Improving the standard of antenatal care and encouraging deliveries in institutions having good NICU facility and early identification of risk factors help to reduce the mortality and its complications.